The structure and thermochemistry of K2CO3–MgCO3 glass - Wilding, M; Phillips, B; Wilson, M; Sharma, G; Navrotsky, A; Bingham, P; Brooker, R; Parise, J (Cambridge University Press, 2019)
Carbonate glasses can be formed routinely in the system K2CO3–MgCO3. The enthalpy of formation for one such 0.55K2CO3–0.45MgCO3 glass was determined at 298 K to be 115.00 ± 1.21 kJ/mol by drop solution calorimetry in molten sodium molybdate (3Na2O·MoO3) at 975 K. The corresponding heat of formation from oxides at 298 K was −261.12 ± 3.02 kJ/mol. This ternary glass is shown to be slightly metastable with respect to binary crystalline components (K2CO3 and MgCO3) and may be further stabilized by entropy terms arising from cation disorder and carbonate group distortions. This high degree of disorder is confirmed by 13C MAS NMR measurement of the average chemical shift tensor values, which show asymmetry of the carbonate anion to be significantly larger than previously reported values. Molecular dynamics simulations show that the structure of this carbonate glass reflects the strong interaction between the oxygen atoms in distorted carbonate anions and potassium cations.